Narratives for healing: an exploration of interactions within an online community on navigating bullying trauma - Sengupta, Subhasree; Yang, Yin (Information Research an international electronic journal, 2025)
Introduction. Online channels can be powerful vessels offering community bonding and support to cope with bullying-induced trauma. Drawing on the theoretical framework of narrative identity, through this initial exploration, we explore the emergent conversational themes of the subreddit (r/bullying) to understand how trauma is disclosed, its impact on the communal identity and the nature of support provided through such online collectives. Method. Data was collected using the Reddit API (praw) from the subreddit r/bullying. A random sample of 50 comments was analysed using thematic coding for this initial exploration. Results. A final set of five themes was developed as an outcome of the analysis. These included a wide array of topics ranging from disclosing deep-rooted resentment and trauma to ways of regaining one’s self-esteem to cope with psychological stress and struggle. Some themes also covered strategies and resources to develop endurance and resilience. Conclusions. These initial insights set the stage for unpacking how narrations of bullying and similar traumatic experiences shape and are shaped by information behavior in mediated contexts (such as online channels), which can hold essential perspectives for conceptualizing the future maintenance and sustenance vision of such virtual spaces.